Features of Parapneumonic Effusions - Petrusevska Marinkovic, Sanja; Kondova Topuzovska, Irena; Stevanovikj, Milena; Anastasovska, Ankica (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/Walter de Gruyter GmbH, 2018)
Abstract Introduction: Parapneumonic effusions, as a complication of community-acquired pneumonia (CAP), usually have a good course, but they sometimes progress into complicated parapneumonic effusion (CPPE) and empyema, thus becoming a significant clinical problem. Aim: To review clinical and radiological features, as well as diagnostic and therapeutic options in parapneumonic effusions. Material and methods: The analysis included 94 patients with parapneumonic effusion hospitalized at the University Infectious Diseases Clinic in Skopje during a 4 year period. Out of 755 patients with CAP, 175 (23.18%), had parapneumonic effusion. Thoracentesis was performed in 94 (53.71%) patients, 50 patients were with uncomplicated parapneumonic effusions (UCPPE) and 44 with complicated parapneumonic effusions (CPPE). Results: More patients (59.57%) were male; the average age was 53.82±17.5 years. The most common symptoms included: fever (91; 96.81%), cough (80; 85.11%), pleuritic chest pain (68; 72.34%), dyspnea (65; 69.15%). Alcoholism was the most common comorbidity registered in 12 (12.77%) patients. Macroscopically, effusion was yellow and clear in most cases (36; 38.29%). Localization of pleural effusion was often in the left costophrenic angle (53; 56.38%) and ultrasonographic non-septated complex. Between the two groups of effusions there was a significant difference between the ERS, WBC and CRP in serum and CRP in pleural fluid. Statistical difference existed in terms of days of hospitalization with a longer hospital stay for patients with CPPE (p <0.0001). Conclusion: Patients with parapneumonic effusion have the symptoms of acute respiratory infection and frequent accompanying diseases. Future diagnostic and therapeutic treatment depends on pleural fluid features and imaging lung findings.